In Vitro Studies of Novel PRKAR1A Mutants that Extend the Predicted RIα Protein Sequence into the 3′-Untranslated Open Reading Frame: Proteasomal Degradation Leads to RIα Haploinsufficiency and Carney Complex - Patronas, Yianna (Endocrine Society, 2012)
BACKGROUND: Carney complex (CNC) is a multiple endocrine neoplasia syndrome due to inactivating mutations in the PRKAR1A gene that codes for type Iα regulatory (RIα) subunit of protein kinase A. Most PRKAR1A mutations are subject to nonsense mRNA decay (NMD) and, thus, lead to haploinsufficiency. METHODS AND SETTING: Patient phenotyping for CNC features and DNA, RNA, protein, and transfection studies were carried out at a research center. RESULTS: We describe in unrelated kindreds with CNC four naturally occurring PRKAR1A mutations (1055del4, 1067del4ins5, 1076delTTins13, and 1142del4) that are predicted to escape NMD because they are located in the last coding exon of the gene. The phenotype of CNC was not different from that in other patients with the condition, although the number of patients was small. Each of the mutations caused a frameshift that led to a new stop codon into the 3′ untranslated open reading frame, predicting an elongated protein that, however, was absent in patient-derived cells. After site-directed mutagenesis, in vitro transcription, and cell-free translation experiments, the expected size mutant proteins were present. However, when the mutant constructs were transfected in adrenal (NCI-295), testicular (N-TERA), and embryonic (HEK293) cells and despite the presence of the mutant mRNA, Western blot analysis indicated that there were no longer proteins. The subsequent application of proteasome inhibitors to cells transfected with the mutant constructs led to the detection of the aberrant proteins, although a compound that affects protein folding had no effect. The wild-type protein was also decreased in both patient-derived cells and/or tissues as well as in the in vitro systems used in this study. CONCLUSIONS: This was the first demonstration of proteasomal degradation of RIα protein variants leading to PRKAR1A haploinsufficiency and CNC, adding protein surveillance to NMD in the cellular mechanisms overseeing RIα synthesis. In agreement with the molecular data, CNC patients bearing PRKAR1A defects that extend the open reading frame did not have a different phenotype, although this has to be confirmed in a larger number of patients.